Light patterning semiconductor nanoparticles by modulating surface charges - Xiaoli He; Hongri Gu; Yanmei Ma; Yuhang Cai; Huaide Jiang; Yi Zhang; Hanhan Xie; Ming Yang; Xinjian Fan; Liang Guo; Zhan Yang; Chengzhi Hu (Nature Communications)
Abstract Optical patterning of colloidal particles is a scalable and cost-effective approach for creating multiscale functional structures. Existing methods often use high-intensity light sources and customized optical setups, making them less feasible for large-scale microfabrication processes. Here, we report an optical patterning method for semiconductor nanoparticles by light-triggered modulation of their surface charge. Rather than using light as the primary energy source, this method utilizes UV-induced cleavage of surface ligands to modify surface charges, thereby facilitating the self-assembly of nanoparticles on a charged substrate via electrostatic interactions. By using citrate-treated ZnO nanoparticles, uniform ZnO patterns with variable thicknesses can be achieved. These multilayered ZnO patterns are fabricated into a UV detector with an on/off ratio exceeding 104. Our results demonstrate a simple yet effective way to pattern semiconductor nanoparticles, facilitating the large-scale integration of functional nanomaterials into emerging flexible and robotic microdevices.